2012
DOI: 10.1007/s10649-012-9454-2
|View full text |Cite
|
Sign up to set email alerts
|

The interplay among gestures, discourse, and diagrams in students’ geometrical reasoning

Abstract: This study identifies forms of interactions with diagrams that are involved in conjecturing; more specifically, how students display their thinking publicly through using multimodal representations. We describe how students interact with diagrams in both gestural and verbal forms, and examine how such multimodal interactions with diagrams reveal their reasoning about diagrams. We hypothesize that when limited information is given in a diagram, students make use of gestural and verbal expressions to compensate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 39 publications
2
20
0
7
Order By: Relevance
“…4, Chen and Herbst (2013) explored the interplay among gestures, discourse and diagram in students' geometrical reasoning. They argued that students make use of gestural and verbal expressions to compensate for the limited information given in a diagram as they engage in making and proving conjectures.…”
Section: Geometry Proof In the Classroommentioning
confidence: 99%
“…4, Chen and Herbst (2013) explored the interplay among gestures, discourse and diagram in students' geometrical reasoning. They argued that students make use of gestural and verbal expressions to compensate for the limited information given in a diagram as they engage in making and proving conjectures.…”
Section: Geometry Proof In the Classroommentioning
confidence: 99%
“…El texto producido puede reflejar sus estilos cognitivos, ya que algunas personas razonan mejor con palabras y otras razonan mejor con figuras (Mayer y Massa, 2003). Así, la interacción entre las representaciones de las configuraciones y el discurso cuando se están resolviendo problemas de probar en geometría aporta información sobre el razonamiento geométrico de los estudiantes, ya que tanto el discurso escrito como las expresiones verbales o gestos pueden considerarse recursos semióticos usados por los estudiantes cuando se implican en la resolución del problema y en comunicar dicha resolución (Chen y Herbst, 2013;Robotti, 2012).…”
Section: Marco Teóricounclassified
“…La manera en la que los estudiantes pueden identificar elementos en una configuración geométrica y asociarlos a hechos geométricos conocidos, o la manera en la que su conocimiento previo de geometría les ayuda a identificar elementos relevantes en una configuración para resolver un problema pueden estar mediadas por sus preferencias cognitivas (Kruteski, 1976), entendidas estas como el modo en que los estudiantes suelen procesar la información (Pitta-Pantazi, Christou, 2009;Mayer y Massa, 2003). Estas preferencias pueden manifestarse en el discurso que los estudiantes generan cuando tienen que comunicar la resolución de un problema (Robotti, 2012;Chen y Herbst, 2013). El texto escrito y las representaciones de las configuraciones como componentes de sistemas semióticos pueden entenderse como instrumentos para la resolución y comunicación de los problemas de probar y, por tanto, son susceptibles de aportar información sobre las características del razonamiento geométrico de los estudiantes (Herbst, 2004).…”
Section: Introductionunclassified
“…One issue in this approach is that the focus tends to be on axioms, syntactic derivations and proofs, and explanatory text is usually missing (Yackel & Hanna, 2003). Explanations and generalizations are used by other researchers when conceptualizing mathematical reasoning to problem solving (Barret, Clements, Klanderman, Pennisi & Polaki, 2006;Bishop, Lamp, Philipp, Whitacre, Schappelle & Lewis', 2014;Bjurland, Cestari & Borgensen, 2008;Chen & Herbst, 2012: Jurdak & Mounhayar, 2014Makar, 2014). This definition is similar to the definition used in this thesis and is further discussed in section 2.1.2.…”
Section: Approaching Reasoning In School Mathematicsmentioning
confidence: 91%
“…Another study in statistics (Chen & Herbst, 2012) examines how high school students made conjectures and justifications through multimodal representations of diagrams during two lessons. The result showed that when limited information is given in a diagram, the students used verbal and gestural expressions to compensate for this limitation when reasoning.…”
Section: Approaching Reasoning In School Mathematicsmentioning
confidence: 99%